Urban Ecosystem Services (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The school of thought surrounding the urban ecosystem has increasingly become in vogue among researchers worldwide. Since half of the world’s population lives in cities, urban ecosystem services have become essential to human health and wellbeing. Rapid urban growth has forced sustainable urban developers to rethink important steps by updating and, to some degree, recreating the human–ecosystem service linkage. Assessing, as well as estimating the losses of ecosystem services can denote the essential effects of urbanization and increasingly indicate where cities fall short. This book contains 13 thoroughly refereed contributions published within the Special Issue “Urban Ecosystem Services”. The book addresses topics such as nature-based solutions, green space planning, green infrastructure, rain gardens, climate change, and more. The contributions highlight new findings for landscape architects, urban planners, and policymakers. Important future cities research is considered by looking at the system connectivity between the social and ecological sphere—via varying forms of urban planning, management, and governance. The book is supported by methods and models that utilize an urban sustainability and ecosystem service-centric focus by adding knowledge-base and real-world solutions into the urbanization phenomenon.